PENGARUH MODAL PSIKOLOGIS DAN PERSEPSI DUKUNGAN ORGANISASIONAL TERHADAP KESUKSESAN KARIR SUBJEKTIF DENGAN ADAPTABILITAS KARIR SEBAGAI PEMEDIASI PADA DOSEN PNS WANITA DI 12 FAKULTAS UNIVERSITAS SYIAH KUALA - Shiva Luthfira; Yurnalis Yurnalis (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to examine the effect of psychological capital and perceived organizational support on subjective career success with career adaptability as a mediator in female civil servant lecturers at 12 Faculties of Syiah Kuala University. Data were obtained through a survey of 196 people as a representative sample of the research population. The data analysis method used is Statistical Product and Service Solutions (SPSS). The results of the study found that psychological capital, perceived organizational support and career adaptability had an effect on subjective career success. Furthermore, the Career Adaptability variable partially mediates between Psychological Capital and organizational support for Career Subjective management.Keywords: Psychological Capital, Perceived Organizational Support, Subjective Career Success, Career adaptability